Informal entrepreneurship and institutional theory: explaining the varying degrees of (in)formalization of entrepreneurs in Pakistan - Williams, Colin C.; Shahid, Muhammad S. (Entrepreneurship and regional development, 2016)
In recent years, scholars adopting institutional theory have explained the tendency of entrepreneurs to operate in the informal sector to be a result of the asymmetry between formal institutions (the codified laws and regulations) and informal institutions (norms, values and codes of conduct). The aim of this article is to further advance this institutional approach by evaluating the varying degrees of informalization of entrepreneurs and then analysing whether lower levels of formalization are associated with higher levels of institutional asymmetry. To do this, a 2012 survey of the varying degrees of informalization of 300 entrepreneurs in Pakistan is reported. The finding is that 62% of entrepreneurs operate wholly informal enterprises, 31% largely informal and 7% largely formal enterprises. None operate wholly formal enterprises. Those displaying lower levels of formalization are shown to be significantly more likely to display higher levels of institutional asymmetry, exhibiting greater concerns about public sector corruption, possessing lower tax morality and being more concerned about high tax rates and the procedural and distributive injustice and unfairness of the authorities. These entrepreneurs tend to be lower-income, younger and less-educated entrepreneurs. The article concludes by discussing the theoretical and policy implications of these findings.